Mengukur Kualitas Aplikasi Berbasis Web Pada E-Tiket Kabupaten Sragen Menggunakan Metode Webqual 4.0 - Nikolaus Triwindi Arvianto; Suprihadi (Syntax Idea)
The research was conducted to analyze the quality of the web application on the Sragen Regency E-Ticket. The research object was conducted at the Communication and Informatics Office of Sragen Regency. Data was collected by distributing questionnaires and tested utilizing the Webqual 4.0 approach with a sample of 72. The independent variables used were usability, quality of information and quality of service interactions. The research data was processed using SPSS and the Blackbox Functional Testing method. The results of the research using the Blackbox Functional Testing method show that if there are several functions of the Sragen Regency E-Ticket website-based application it still cannot run as the website-based application is designed and the results of data processing utilizing the Webqual 4.0 approach show that the usability and information quality variables do not significantly affect satisfaction of all users, while the variable quality of service interaction has a significant effect on the satisfaction of all users.